AN AN OBSERVATIONAL STUDY OF PRESCRIPTION PATTERN OF DRUGS FOR OSTEOARTHRITIS IN A NORTH INDIAN MEDICAL COLLEGE - ASHWANI UMMAT; RANJODH JEET SINGH; SONIA KOCHHAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study is to analyze the prescription pattern of drugs for osteoarthritis (OA) in a north Indian medical college collaborated with a tertiary care hospital. Methods: An observational study was conducted on 300 patients diagnosed with OA in the department of orthopedics in collaboration with the department of pharmacology, and thus, prescription was collected as in a cross-sectional manner for 6 months and the same were analyzed in the Department of Orthopedics in tertiary care hospital collaborated with medical college. Results: The average age of patients participating in this present study was 56.46±7.4 years with affected age group of 46-60 years. 60 % of females were affected by osteoarthritis outnumbering male (40 %) patients in this present study. The most commonly involved joint was knee joint (87.33 %) in patients diagnosed with osteoarthritis followed by back (6.67 %) and hip joint (6%). The combination therapy (90 %) outweighed monotherapy (10 %) with preferred route of drug administration as oral route (90 %) followed by topical route (10 %). The average number of drugs prescribed for patients of osteoarthritis was 2.62±0.76. This present study concludes that NSAIDs (45.8%) were prescribed most commonly. However, the drug paracetamol was lesser prescribed and other drugs such as Diclofenac (27.22 %) and acetaminophen (34.44 %) most of all followed by Nimesulide (16.67 %), ibuprofen (13.33 %) and Rofecoxib/valdecoxib (8.33 %) were prescribed. Conclusion: This present study concludes that NSAIDs were most commonly prescribed as p-drugs while paracetamol was undermined prescribed.